SCREENING OF ANTIOXIDANT PROPERTY IN MEDICINAL PLANTS BELONGING TO THE FAMILY APOCYNACEAE ZAHRA - Iqbal, Zahra; Iqbal, Mohammed Shariq; Mishra, Kumkum (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The present study was aimed to explore antioxidant properties of the plants belonging to the family Apocynaceae. Methods: Plants used in the study were Alstonia scholaris, Calotropis gigantea, Catharanthus roseus, Cerbera odollam, and Wrightia tinctoria. The plant material was used to estimate non-enzymatic antioxidant, namely, total antioxidant, total flavonoids, total phenolic, and total carotene content using spectrophotometer. Result: The results showed significant antioxidant potential of the plants used in the study. It was observed that total flavonoids content was maximum in W. tinctoria (65.21 ± 3.712 mg equivalent quercetin/g of tissue), while total phenolic content was found maximum in C. roseus (59.63 ± 2.151 mg equivalent gallic acid/g of tissue). When total carotene content and total antioxidant activity were estimated, it was found maximum in C. roseus with (70.91 ± 4.41 μg/g fresh weight) and (0.846 ± 0.109 mM equivalent ascorbic acid/g tissue), respectively. Conclusion: It was observed C. roseus possess potent antioxidant property compared with other plants of same family. When correlation was established between the antioxidants and different genera plants, a strong positive correlation was observed, indicating that the plants belonging to the family Apocynaceae are a potent source of antioxidants. Further research is recommended to explore this family (Apocynaceae) and to fully elucidate its biochemical (antioxidant) benefits.